Leptomeningeal Carcinomatosis in Urothelial Carcinoma of the Urinary Bladder: A Report of a Patient with a Fulminant Course Who Died of Cancer after Definitive Therapies - Masayuki Tomioka; Makoto Kawase; Daiki Kato; Manabu Takai; Koji Iinuma; Kengo Horie; Keita Nakane; Natsuko Suzui; Tatsuhiko Miyazaki; Takuya Koie (Case Reports in Urology)
A 45-year-old Japanese man visited a community hospital with the chief complaint of asymptomatic macrohematuria. He was diagnosed with muscle-invasive bladder cancer (MIBC), and he received intra-arterial chemotherapy followed by radiation therapy at another institution. Twenty-eight months after chemoradiotherapy, magnetic resonance imaging (MRI) revealed MIBC recurrence. After neoadjuvant chemotherapy, robot-assisted radical cystectomy was performed. Pathological examination indicated high-grade urothelial carcinoma with lymphovascular invasion, a positive surgical margin, and skip lesions of cancer cells in the perivesical adipose tissue. Three months after surgery, he was brought to our hospital in an ambulance with the chief complaint of rotatory vertigo and was speaking inarticulately. Head and whole spine MRI revealed meningeal metastasis along both the vestibulocochlear nerves and cauda equina. Analysis of the cerebrospinal fluid revealed malignant cells. The patient was diagnosed with leptomeningeal carcinomatosis originating from the MIBC. He received whole-brain radiotherapy followed by the administration of pembrolizumab. Unfortunately, the patient’s condition quickly deteriorated, and he died of cancer 4 months after surgery.